TEXTURALISM - COZMA, Andrei C. (Studia Universitatis Babes-Bolyai Musica, 2013)
Although identifying and defining texture as a specific sound organization in sound mass compositions comes about frequently in contemporary musicology, only a handful of researchers regard this as a tendency of what turns out to be a large number of composers towards an aesthetic with underlying principles of composition. A delimitation of a notion that includes such a diversity of compositional methods into a stylistic unity still tapped into by composers is achieved by analysing some particular characteristics of a few textural pieces and other attributes that are common to various other pieces. The suggested theory of texturalism thus systemizes an important part of the 20th century music in which compositional techniques of other style defining musical practices are grouped together with singular technical features.